Network Intrusion Detection System Based on Matching Logical Address and Port Number - Boskany, Najmadin Wahid Abdulrahman (Sulaimani Journal for Pure and Applied Sciences, 2009)
The aim of this paper is to design a significant system for detecting intrusion hosts inside computer networks. The goal is to let network administrators detect and discover if possible hackers (unauthorized hosts) that attempt to break into network infrastructure exist or no, who observe network traffic or try to cause service attack, by accident or with purpose. Keywords: Network Intrusion Detection System (NIDS), Logical Address, Network Interface Card (NIC), Firewall, Application Programming Interface (API), Dynamic Link Library (DLL).